Digital and Non-Digital Leadership in Merdeka Curriculum Implementation: A Case Study at Al-Bahjah Cirebon - Sulfiani, Sulfiani; Nurdin, Muh. Nur Islam; Fajruddin, Muhammad Nabhan; Fauziana, Sartika Putri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study aims to describe and analyze the practices of principal leadership in the implementation of the Merdeka Curriculum at SMA Islam Qur'ani Al-Bahjah Cirebon, focusing on the dynamics of digital and non-digital leadership. The research employs a descriptive qualitative method with a single case study design, utilizing interviews, observation, and documentation involving the principal, vice principal for curriculum affairs, and teachers. The results indicate that non-digital leadership remains dominant as it aligns with the values of discipline and the pesantren (Islamic boarding school) character. Conversely, digital leadership is used to a limited extent for the efficiency of communication and administration, but is constrained by infrastructure and internal policies. The findings affirm the emergence of a hybrid leadership model where both approaches complement each other according to the context. This study emphasizes the importance of flexibility in educational leadership when adopting digitalization without abandoning traditional pesantren values